Development of PowerPoint-based Comic Media - Leni Friska Aprilliana; Ida Putri Rarasati (Universitas Islam Balitar, 2021)
This study aims to develop a PowerPoint-based comic for learning PPKn lesson. To achieve this objective, research and development was applied. This study engaged several validators to assess the content, media, and language of the product. In this process, validation sheets were distributed to the validators. The results of validation revealed that the content was moderately feasible, the media (display) was very feasible, and the language was feasible. Regarding this result, PowerPoint-based comic media can be used as a learning media for PPKn lesson.